ASSIGNMENT OF STOCK KEEPING UNITS TO PARALLEL UNIDIRECTIONAL PICKING - Matthews, Jason; Visagie, Stephan E (The South African Journal of Industrial Engineering, 2015)
An order picking system consisting of a number of parallel unidirectional picking lines is investigated. Stock keeping units (SKUs) that are grouped by product type into distributions (DBNs) are assigned daily to available picking lines. A mathematical programming formulation and its relaxations is presented. A greedy insertion and a greedy phased insertion are further introduced to obtain feasible results within usable computation times for all test cases. The walking distance of the pickers was shown to decrease by about 22 per cent compared with the current assignment approach. However, product handling and operational risk increases.